Quality properties of cookies supplemented with fresh brewer's spent grain - Petrović Jovana S.; Pajin Biljana S.; Tanackov-Kocić Sunčica D.; Pejin Jelena D.; Fišteš Aleksandar Z.; Bojanić Nemanja Đ.; Lončarević Ivana S. (Food and Feed Research, 2017)
Brewer's spent grain (BSG) is a by-product generated during the brewing process. It is a rich source of dietary fibre and proteins, with great potential to increase nutritional value of food products. In this research different quantities of fresh (non-dried and non-milled) brewer's spent grain (15, 25 and 50%) were added to wheat flour on a replacement basis in order to evaluate its effect on fibre and protein content, instrumental parameters of colour, microbial stability and sensory characteristics of cookies. Protein and fibre content of cookies increased following the addition of BSG from 7.55% to 9.69% and 6.8 to 15.55%, respectively. Considering the colour characteristics, addition of BSG decreased L*and b* values, while a*values increased. Enterobacteriaceae, Escherichia coli, Clostridium spp., yeasts and moulds were not detected in cookie samples, while the Enterobacteriaceae were detected (40 cfu/g) in fresh BSG. The addition of 25% of BSG resulted in best sensory characteristics of cookies in terms of surface appearance, hardness, grittiness and flavour. The results have shown that fresh BSG has a potential to increase nutritional value of the cookies without negative influence on cookie sensory characteristics and microbiological stability.